Seeds for Needs: Climate-smart agriculture for poor rural communities in Laos and Cambodia. Progress Report - Bioversity International (2015)
With the generous support of XXX, Bioversity International is undertaking research in Cambodia and Laos to improve the livelihoods of poor smallholder farmers, and to assist them in adapting to environmental stresses induced by climate change in order to achieve sustainable nutrition and livelihoods. The project aims to identify, test and disseminate seed varieties that are best adapted to a broad range of environmental conditions, using Geographic Information System (GIS) technology, environmental data and information management. Training will be provided to increase the capacity of government decision-makers and technical staff, and several awareness-raising activities for communities undertaken. Ultimately, a farmer-based ‘experimentation network’ in the Mekong River Basin region for the testing of selected planting materials will be established. This is the second technical report, which summarizes and reviews the activities, progress and achievements of the second year of the project, covering the period from 1 January 2014 to 31 December 2014.